2009
DOI: 10.3147/jsfp.44.86
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Expression of Shrimp-virus Antigens in Two Insect Cell Lines Challenged with Two Shrimp Viruses

Abstract: ABSTRACT-Experiments with crustacean viruses are hampered by lack of susceptible continuous cell lines. To overcome this problem, immortal mosquito and lepidopteran cell lines were both separately challenged with a shrimp DNA virus (white spot syndrome virus: WSSV, = PRDV) and RNA virus (yellow head virus: YHV) followed by serial, split-passage with immunohistochemical monitoring by confocal laser microscopy using labeled monoclonal antibodies to shrimp viral antigens. Stable, immortal cultures with 100% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
17
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 26 publications
8
17
1
Order By: Relevance
“…In contrast to whole cells, culture supernatant solutions were negative for YHV using the same RT-PCR protocol, suggesting that YHV target material was not released into the culture medium, at least not in sufficient quantity to be detected by the methods used. This result corresponded to previous results showing a lack of recognizable YHV viral particles or nucleocapsids in YHV-imunopositive C6/36 cells by transmission electron microscopy (Sriton et al 2009) and suggested that transmission of YHV in the insect cells most likely occurred during daughter cell production or by endocytosis.…”
Section: Persistent Infections Of Yhv In C6/36 Cellssupporting
confidence: 92%
See 4 more Smart Citations
“…In contrast to whole cells, culture supernatant solutions were negative for YHV using the same RT-PCR protocol, suggesting that YHV target material was not released into the culture medium, at least not in sufficient quantity to be detected by the methods used. This result corresponded to previous results showing a lack of recognizable YHV viral particles or nucleocapsids in YHV-imunopositive C6/36 cells by transmission electron microscopy (Sriton et al 2009) and suggested that transmission of YHV in the insect cells most likely occurred during daughter cell production or by endocytosis.…”
Section: Persistent Infections Of Yhv In C6/36 Cellssupporting
confidence: 92%
“…Although it is not proposed that these cultures should or would replace YHV extracts or purified YHV as inoculum for challenge tests with shrimp, the cultures might constitute a convenient, additional tool for laboratory studies on some topics, such as aspects of hostviral interaction and efficacy of double-stranded RNA constructs for knockdown of viral antigens. It remains to be determined whether homogenates of early passages of Sf9 cells persistently immunopositive for YHV antigens (Sriton et al 2009) would also cause YHD in shrimp. …”
Section: Challenge Test Resultsmentioning
confidence: 99%
See 3 more Smart Citations